THE EFFECT OF CONCENTRATION OF POLYMERS - Эшдавлатова Гулрух Эшмаматовна (Web of Journals Publishing, 2023)
Chemical activation of starch suspension and its effects were studied. The effect of the concentration of water-soluble polymers in the development of thickeners was determined. The effect of chemical treatment time on the properties of the resulting suspensions was determined. The influence of the concentration of thickeners on the modification process was studied.
Keywords: Polymer composition, cotton, nitron fiber, fabric, paint, thickener, ludigol, thixotropic recovery.